MEDB-61. Genetic alterations ofTP53 andOTX2 indicate increased risk of relapse in WNT medulloblastomas. (3rd June 2022) - Goschzik, Tobias; Mynarek, Martin; Dörner, Evelyn; Aretz, Stefan; Rutkowski, Stefan; Pietsch, Torsten
Abstract: PURPOSE: This genetic analysis of WNT-activated medulloblastomas (WNT-MBs) aimed to re-evaluate the prognostic impact of TP53 mutations and to identify specific chromosomal aberrations as possible prognostic markers in a retrospective cohort of patients treated according to the protocols of the HIT medulloblastoma studies. PATIENTS AND METHODS: In a cohort of 191 patients with WNT-MBs, mutations in CTNNB1, APC, and TP53 were analyzed by Sanger and/or NGS panel sequencing. Chromosomal copy number aberrations (CNAs) were assessed by high-resolution, genome-wide molecular inversion probe technology (MIP), SNP6 array, and/or 850k methylation bead-array hybridization. Complete clinical data were available from 120 patients. RESULTS: Patients with WNT-MBs had a female predominance (1.4:1) and a median age of 13 years (range 3-69 years). CTNNB1 mutations were present in 92.2% of the samples, APC mutations in 6.8%. One CTNNB1 wildtype tumor gained WNT-activation due to a homozygous deletion of FBXW7 . Monosomy 6 was present in 78.6%, but more frequent in children compared to adults. 16.1% of the tumor samples showed TP53 mutations, of those 60% with nuclear positivity for the p53 protein. A loss of heterozygosity at the TP53 locus on chromosome 17p13.1 was found in 40.7% (11/27) of TP53 mutant tumor samples and in 18.5% of the whole cohort (24/130 cases). Patients with tumors harboring TP53 mutations showed significant worse progression-free survival (PFS; p=0.001), but not overall survival (OS) and were enriched for chromosomes 17p (p=0.001), 10, and 13 losses. Gains of the OTX2 locus on chromosome 14q were also associated with poor PFS and OS (p=0.017 resp. p=0.006). Multivariate Cox regression analysis identified both genetic alterations as independent prognostic markers for PFS and OS. CONCLUSION: For ongoing and future de-escalation trials for patients with WNT medulloblastomas, we recommend to exclude patients with tumors carrying TP53 mutations or OTX2 gains.